Spolien Phänomene der Wiederverwendung in der Architektur - Meier, Hans-Rudolf 1956- (Jovis, 2020)
Spolia are structural elements that have been consciously-and therefore usually visibly-reused. The space they occupy within the broad field of reuse in architecture is associated with specific intentions regarding design and significance. As they are usually visibly distinct from the rest of the construction, spolia encourage viewers to augment their understanding with additional meanings. As contemporary architecture has returned to incorporating ornamentation and history, the use of spolia has also increased. To date, spolia have been considered with reference to late antique, medieval, and-much more rarely-modern architecture. In this work, the uses of spolia throughout different time periods are considered in relation to one another. In addition to aspects of cultural studies, this volume illuminates the role of spolia in the design process